Employee-owned companies: A potential solution to minimising industrial action in South Africa - Sebesho, Bonga (University of the Witwatersrand, Johannesburg, 2016)
The purpose of this research was to assess the employee-owned company model as a potential solution to minimise industrial action in South Africa. Employee ownership, positioned as a key pillar of broad-based black economic empowerment (BBBEE) (Mosai & Reynolds, 2003), is linked to increased employee participation and ultimately to improved industrial relations as a result of increased engagement between employers and employees. Research was undertaken through a study of the multiple methods in which employee ownership is implemented across various industries in South Africa taking into account the reasons for the implementation of employee ownership. This research attempted to cover a wide spectrum of employee ownership models ranging from once-off employee share ownership schemes (ESOPs) to closed employee ownership schemes. Qualitative data was collected through in-depth interviews, utilising the Delphi technique, with a sample of 11 respondents who have been involved in the implementation of employee ownership schemes. The data was content-analysed and the findings suggested that employee ownership has the ability to engender increased participation. The findings of the study suggest that the successful implementation of employee ownership in South Africa has been severely impacted by historical issues relating to financial preparedness from employees and the deep entrenchment of the shareholder value as well as the compliance burden from a business perspective. The study concludes that employee ownership can play a role in engendering meaningful economic participation and consequently reduce the incidence of industrial action. However, in order to achieve its desired objective the government will need to put in place effective incentives as well as powerful disincentives to encourage implementation of long term ownership schemes. This study may provide guidance to South African companies, government and other stakeholders seeking to find broad-based and inclusive models in order to increase employee representation and participation in corporate decision making. The research findings may assist these organisations to find new ways to create a more inclusive economic environment through leveraging the benefits of employee ownership to decrease the incidence of industrial action and ultimately improve output.
This research report is submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in the Wits Business School, in partial fulfilment of the requirements for the degree of Master of Business Administration, in 2016.
Keywords: Employee-owned company model; Broad-based black economic empowerment (BBBEE); Employee share ownership schemes (ESOPs); Employee ownership; South African companies; UCTD